Heterosynaptic modulation in the paraventricular nucleus of the hypothalamus. (August 2019) - Sunstrum, Julia K.; Inoue, Wataru
Abstract: The stress response—originally described by Hans Selye as "the nonspecific response of the body to any demand made upon it"—is chiefly mediated by the hypothalamic-pituitary-adrenal (HPA) axis and is activated by diverse sensory stimuli that inform threats to homeostasis. The diversity of signals regulating the HPA axis is partly achieved by the complexity of afferent inputs that converge at the apex of the HPA axis: this apex is formed by a group of neurosecretory neurons that synthesize corticotropin-releasing hormone (CRH) in the paraventricular nucleus of the hypothalamus (PVN). The afferent synaptic inputs onto these PVN-CRH neurons originate from a number of brain areas, and PVN-CRH neurons respond to a long list of neurotransmitters/neuropeptides. Considering this complexity, an important question is how these diverse afferent signals independently and/or in concert influence the excitability of PVN-CRH neurons. While many of these inputs directly act on the postsynaptic PVN-CRH neurons for the summation of signals, accumulating data indicates that they also modulate each other's transmission in the PVN. This mode of transmission, termed heterosynaptic modulation, points to mechanisms through which the activity of a specific modulatory input (conveying a specific sensory signal) can up- or down-regulate the efficacy of other afferent synapses (mediating other stress modalities) depending on receptor expression for and spatial proximity to the heterosynaptic signals. Here, we review examples of heterosynaptic modulation in the PVN and discuss its potential role in the regulation of PVN-CRH neurons' excitability and resulting HPA axis activity. This article is part of the Special Issue entitled 'Hypothalamic Control of Homeostasis'. Graphical abstract: Image 1 Highlights: The hypothalamic-pituitary-adrenal axis mediates the neuroendocrine response to diverse stimuli that signal threats. This diversity is achieved by the complexity of inputs that converge onto the paraventricular nucleus of the hypothalamus. Besides forming canonical synapses, these inputs also modulate each other's transmission through heterosynaptic modulation. We define heterosynaptic modulation as one neurotransmitter system that regulates the activity of others. Here, we review examples of heterosynaptic modulation in the paraventricular nucleus of the hypothalamus.